2015
DOI: 10.4055/cios.2015.7.3.323
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Interspinous Dynamic Stabilization

Abstract: BackgroundA systematic literature review of interspinous dynamic stabilization, including DIAM, Wallis, Coflex, and X-STOP, was conducted to assess its safety and efficacy.MethodsThe search was done in Korean and English, by using eight domestic databases which included KoreaMed and international databases, such as Ovid Medline, Embase, and the Cochrane Library. A total of 306 articles were identified, but the animal studies, preclinical studies, and studies that reported the same results were excluded. As a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Our study found that complications related to surgery or to the device were very few, with only four patients presenting intraoperative complications (spinal fluid leak) which were unrelated to specific use of IntraSPINE ® . This is consistent with the results of Leeet al who reported no complications such as myocardial infarction, pulmonary embolism, cerebrovascular accident, acute renal failure, mortality, deep venous thrombosis, ileus or urinary tract infection [20].…”
Section: Discussionsupporting
confidence: 93%
“…Our study found that complications related to surgery or to the device were very few, with only four patients presenting intraoperative complications (spinal fluid leak) which were unrelated to specific use of IntraSPINE ® . This is consistent with the results of Leeet al who reported no complications such as myocardial infarction, pulmonary embolism, cerebrovascular accident, acute renal failure, mortality, deep venous thrombosis, ileus or urinary tract infection [20].…”
Section: Discussionsupporting
confidence: 93%
“…The most frequent complications were implant related complications in both groups. On the one hand, studies on IDSS,such as Diam, Wallis, and Coflex; reported an implant related complication rate up to 32.3% [ 32 ]. On the other hand, Gelais et al in a systematic review, reported that rates of screw malposition in fusion surgery, vary considerably, they found the percentage of screws fully contained in the pedicle ranged from 28 to 85% [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…These procedures have been proposed as minimally invasive alternative procedures to laminectomy and fusion (Landi 2014). By distracting the adjacent spinous processes and/or lamina and thereby restricting extension in patients with lumbar spinal stenosis and neurogenic claudication, these interspinous distractor devices can alleviate symptoms that arise from neural compression (Lee et al 2015). These devices enlarge the neural foramen, decompress the causa equina, and act as spacers between the spinous processes to limit extension of the spinal interspace.…”
Section: Spine Products Approved Outside the United Statesmentioning
confidence: 99%
“…Because of the minimally invasive nature of placement of these devices, proponents argue that such techniques lead to shorter hospital stay, preservation of local bone and tissue, reduced risk of cerebrospinal fluid leakage, and is reversible in such a way that it does not limit future treatment options. Some potential complications of these spacer devices are fracturing of spinous processes, incorrect positioning, and mechanical failure of the devices (Lee et al 2015).…”
Section: Spine Products Approved Outside the United Statesmentioning
confidence: 99%